MENELISIK MAKNA HIJRAH DALAM AL-QUR’AN: Studi Komparatif Atas Penafsiran Ibnu Katsir dan Quraish Shihab - Hasbullah Hasbullah; Sofuan Jauhari (Ushuly: Jurnal Ilmu Ushuluddin, 2023)
The trend of hijrah being a new choice in the life of a Muslim today hijrah is connoted with repentance, which tends to be synonymous with significant changes to the way of dressing that was not closed aurat, dressed tight, now changed to cover aurat, dress more Syar'i with a long veil and loosely dressed, some even wear veils. This research uses qualitative methods with this type of library reaserch and uses data collection techniques with the collection of records, books, books and others referring to the research of Maryam verse 46, al-Mu'minun verse 67, al-Furqon verse 30, al-Muzzammil verse 10, and al-Muddatsir verse 5 by consolidating the interpretation of Ibn Katsir Muhammad Quraish Shihab.